Prazosin dosed 3 times a day to treat flashbacks related to PTSD: A case report - Christie Richardson, DO, MS; Alexander Swartz, BA; Martin Forsberg, MD (American Association of Psychiatric Pharmacists, 2023)
Prazosin is an alpha-1 adrenergic receptor antagonist widely known by mental health providers for its off-label use for nightmares in patients with PTSD. Prazosin is lipophilic and crosses the blood-brain barrier to antagonize alpha-1 receptors in the central nervous system, potentially reducing autonomic arousal caused by PTSD. There have been numerous case reports describing the reduction of nightmares and daytime flashbacks due to PTSD with prazosin dosed at night and during the day, respectively. This case report illustrates the resolution of flashbacks related to chronic PTSD with prazosin dosed 3 times a day. As the half-life of prazosin is only 2 to 3 hours, even a twice daily dosing regimen may lead to breakthrough symptoms between doses. This case proposes a unique dosing strategy for prazosin and need for further research utilizing multiple daily doses of prazosin in the treatment of PTSD.